2020
DOI: 10.1080/02568543.2020.1773588
|View full text |Cite
|
Sign up to set email alerts
|

Families’ Experiences of a Universal Play-based Early Childhood Program in Nova Scotia: Implications for Policy and Practice

Abstract: This study examined families' experiences of a publicly funded, play-based early learning program for children in the year before school entry. An online survey was conducted with parents and/or guardians (n = 291) to learn about their child's outcomes in the program, their perception of play-based learning, attitudes toward the program, and how the program supported their family. Socio-demographic information was also collected (income, education). A concurrent triangulation mixed methods design was used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
6
0
5
Order By: Relevance
“…We provided contextual information on the Pre-primary Program information to inform the transferability to similar system-wide efforts to improve access to ECEC programs. Our work builds on previous research on this initiative in Nova Scotia by reinforcing the importance of communication with families about the program, including the importance of play-based learning within ECEC programs (Carolan et al, 2019). Because the Pre-primary Program is located in school settings, it also provides a unique contribution to the literature of the value that parents have on the location of the program and how this characteristic supports children's familiarity with school programs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We provided contextual information on the Pre-primary Program information to inform the transferability to similar system-wide efforts to improve access to ECEC programs. Our work builds on previous research on this initiative in Nova Scotia by reinforcing the importance of communication with families about the program, including the importance of play-based learning within ECEC programs (Carolan et al, 2019). Because the Pre-primary Program is located in school settings, it also provides a unique contribution to the literature of the value that parents have on the location of the program and how this characteristic supports children's familiarity with school programs.…”
Section: Discussionmentioning
confidence: 73%
“…Further studies have suggested that some parents only value play if it does not interfere with learning academic skills (Baker, 2014, Kane, 2016, Yahya, 2016. Parental perspectives appear to be influenced by a number of factors, and previous research on the Pre-primary Program has found that positive views on play may be influenced by parents' connection to the school community and communication with a child's educators (Carolan et al, 2019). The varied family perspectives on play-based learning in our study and other ECEC programs highlights the importance of further research to study the ways to further understand and learn more about the concerns of parents and ways to work together to ensure high quality, play-based ECEC programs.…”
Section: Discussionmentioning
confidence: 99%
“…The play has long been regarded as a critical element of early childhood curriculum and pedagogy (Dockett & Perry, 2010). Defining play and play-based learning is not straightforward (Carolan et al, 2020). Much of what we know about play and its relationship with learning has its roots in theorists such as Piaget, Vygotsky and Bandura, who underline the role of play, investigation and exploration, the role of language and communication.…”
Section: The Play-based Learning At the Age Of Infancy And Nursery Te...mentioning
confidence: 99%
“…Similarly, Casey et al (2008) used block-building interventions in relation to storytelling and they indicated that storytelling provided an effective context for teaching geometrical concepts and spatial sense. Carolan et al (2020) examined families' experiences of a funded play-based early learning program for children in the year before school entry. Results indicated mainly the importance of good communication with teachers in order to understand the playbased framework.…”
Section: The Play-based Learning At the Age Of Infancy And Nursery Te...mentioning
confidence: 99%
“…As an example, the Canadian federal government through their Canada-Wide ELCC agreements with provincial and territorial governments has committed to work towards the creation of an affordable, accessible, high-quality, and inclusive system of ELCC (Doering, 2021). Further, universally funded programs targeting children prior to entry into the formal school system (typically four-years old or Pre-Kindergarten age) and co-located in existing school settings is a recent model for the delivery of ELCC (Carolan et al, 2020;Corter et al, 2012;Peters et al, 2016). Although there is an established body of research examining the general concept of quality (Layzer & Goodson, 2006; Slot, 2018), there is less known about specific quality elements reflected within ELCC programs that are universally funded and co-located in schools.…”
mentioning
confidence: 99%